Gamma-H2AX: A potential biomarker in breast cancer. Issue 9 (September 2019) - Varvara, Palla Viktoria; Karaolanis, Georgios; Valavanis, Christos; Stanc, Gabriela; Tzaida, Olympia; Trihia, Helen; Patapis, Paul; Dimitroulis, Dimitrios; Perrea, Despoina
Histone H2AX undergoes phosphorylation as an answer to DNA double-strand breaks, which in turn are part of the oncogenic procedure. The detection of gamma-H2AX can potentially serve as a biomarker for transformation of normal tissue to premalignant and consequently to malignant tissues. The aim of this study was to evaluate the clinical significance of gamma-H2AX expression in breast cancer. Gamma-H2AX expression in tissues from 110 breast cancer patients was analyzed by immunohistochemistry and correlated with clinicopathological variables. Greater tumor size, higher grade, and the number of affected lymph nodes are significantly associated with greater values of gamma-H2AX. In addition, gamma-H2AX differs significantly among patients' International Federation of Gynecology and Obstetrics stage. Higher values of estrogen receptor and progesterone receptor are significantly associated with lower gamma-H2AX values. In conclusion, a positive association between gamma-H2AX expression and infaust histopathological parameters was observed.